2005
DOI: 10.1039/b3rp90001k
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and computer-assisted learning in teaching acids and bases

Abstract: The traditional and the computer-assisted teaching methods for teaching a fundamental topic within chemistry education, acids and bases, were compared and the influences of the three dimensional spatial visualization abilities, computational attitudes and learning styles of the students on their acquisition of knowledge were investigated. The students were randomly distributed into control and experimental groups and their knowledge about acids and bases was assessed by a test comprising twenty questions. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The results revealed that students in the experimental group performed significantly better in all topics than their schoolmates who were taught the same topics by the conventional approach. This finding was consistent with the earlier reports of Barnea and Dori (1999), Chang (2001), Morgil et. al.…”
Section: Discussionsupporting
confidence: 83%
“…The results revealed that students in the experimental group performed significantly better in all topics than their schoolmates who were taught the same topics by the conventional approach. This finding was consistent with the earlier reports of Barnea and Dori (1999), Chang (2001), Morgil et. al.…”
Section: Discussionsupporting
confidence: 83%
“…In the literature, there are few studies that applied Kolb's Learning Style Inventory (LSI) questioner (Kolb and Kolb 2005) in order to perceive students' learning styles in chemistry or science education. Morgil et al (2005) noted that students commonly possessed the assimilator and diverger learning styles when they compared the effects of the traditional and computer-assisted method of teaching on students' achievement in acid-base chemistry topic. Similar findings were presented by Kaya et al (2009) who noted that males and females had the most diverger and assimilator learning styles when they examined variations of primary school students' learning styles according to gender in science and technology lessons.…”
Section: Conclusion Of Study Resultsmentioning
confidence: 98%
“…Ozge Ozyalcın Oskay et al, 2011 in their study used flow map to determine the cognitive structures of prospective chemistry teachers about the topics of bonding and hybridization [17]. The topic was explained to the students in control group via traditional method.…”
Section: Webmentioning
confidence: 99%